Ectopic BH3-only protein Bim acts as a cochaperone to positively regulate Hsp70 in yeast. (29th June 2021) - Pan, Hao; Song, Ting; Wang, Ziqian; Guo, Yafei; Zhang, Hong; Ji, Tong; Cao, Keke; Zhang, Zhichao
Abstract: The chaperone heat shock protein 70 (Hsp70) is conserved from bacteria to humans and is crucial for avoiding protein misfolding under stress. Bim functions, mainly as one of the B-cell lymphoma 2 (Bcl-2) family proapoptotic members, were identified to be a cochaperone of Hsp70. Herein, we reported that ectopic Bim could constitute the interactions with intrinsic Hsp70 and translate its positive cochaperone activity in vitro to the yeast growth promotion and help Hsp70 to fold its client Ras-like protein. With the help of a specific Hsp70/Bim disruptor, we illustrated that Hsp70/Bim dimers rescue yeast from heat shock. In an organism lacks apoptotic Bcl-2 factors, the proapoptotic Bim in mammalian cells exhibits prosurvival functions. Graphical Abstract: